Kesesuaian Butir Soal Evaluasi Mata Kuliah Menulis Bahasa Mandarin Tahun Pertama dengan Kurikulum Internasional Pendidikan Bahasa Mandarin - Estherlyn, Eunike (Fenghuang: Jurnal Pendidikan Bahasa Mandarin, 2022)
The Mid-Semester Examination (UTS) and The Final Examination (UAS) are part of the learning evaluation. The evaluation aims to measure the achievement of student competence. Therefore, the questions made by theteacher must be following with the teaching materials, content, and curriculum objectives. This study aims to describe the alignment of the writing test items level one (UTS and UAS) with International Chinese Language Education (KIPBM). The questions for thelevel one Mandarin Writing—which are limited to Writing basic 1 and 2—are used for the data. The data is classified based on the type of writing questions and the indicator of writing competence achievement (IPK) KIPBM. The findings of this study are that in the UTS and UAS Writing basic 1 and 2; there are six types of evaluation tests aligned for Mandarin writing basic level one. Based on the alignment of questions with the indicator of writing competence achievement (IPK), in the UTS and UAS Writing basic 1; there are 315 questions, 40 questions IPK-1 related, 19 questions IPK-2 related, 40 questions IPK-3 related, and 48 questions IPK-4 related. Meanwhile, in the UTS and UAS Writing basic 2; there are 342 questions IPK-1 related, 257 questions IPK-2 related, 332 questions IPK-3 related, and 70 questions IPK-4 related.